Highly filled elastomeric matrix composites: Structure and property evolution at low temperature carbonization. (15th October 2018) - Chukov, D.I.; Stepashkin, A.A.; Salimon, A.I.; Kaloshkin, S.D.
Abstract: A new approach for the development of carbon composites via a low-temperature carbonization of elastomer compounds highly filled with various carbon fillers and dispersed SiC was systematically implemented. A new class of economically attractive carbon composites was purposely designed and relevant low-temperature carbonization approach was systematically applied for elastomer compounds highly filled with various carbon fillers and dispersed SiC. It was shown that carbonization in the range of 320–360 °С results in a combination of sound structure and optimal properties. The composites carbonized at 360 °С were thoroughly studied in terms of structure, mechanical and thermal properties. The values of the tensile and the flexural strength of the composites lie in the range of 65–85 MPa and 75–125 MPa, respectively. Positive effect of SiC fillers on the thermal expansion behavior of the carbonized composites was found. The coefficient of thermal expansion for SiC-containing composites was around 20–35 ∗ 10 −6 in the temperature range of 30–300 °C. Obtained combination of service properties assumes a range of applications in machine building and in the construction of high-demand mechanical parts. Graphical abstract: Highlights: New inexpensive carbon composites are designed as competitors for CF-PEEK composites and Mg alloys Special compounding of rubber composites and further low temperature carbonization constitute the core of new approach Structure and properties evolution against carbonization temperature up to 420 °С is thoroughly studied Carbonization at 320-360 °С results in good engineering properties - strength,  stiffness and maximum service temperature